Enhancing Pedagogical and Content Knowledge through Preservice Training: A Study on Islamic Religious Teacher Candidates - Hendri Kuswiran; Qolbi Khairi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Improving the competencies of future teachers requires innovative approaches, including preservice training aimed at strengthening Pedagogical Content Knowledge (PCK)—a fusion of subject matter expertise and pedagogical skills. This study investigates the effectiveness of preservice training in enhancing PCK among prospective Islamic Religion teachers. A quantitative, one-group pre-test–post-test design was implemented involving 45 students from the Islamic Education Department at Fatmawati Sukarno State Islamic University, Bengkulu, Indonesia. Participants were selected using purposive sampling to target a specific population. Data were collected through tests measuring both content and pedagogical knowledge and analyzed using paired sample t-tests and descriptive statistics. Post-test results indicated a significant improvement in both content and pedagogical knowledge compared to pre-test scores. Statistical analysis yielded a significance value of 0.000 (p 0.05), confirming the training's effectiveness in developing students' PCK. The findings demonstrate that preservice training plays a vital role in advancing prospective Islamic teachers' integrated understanding of subject matter and pedagogy. These results support the inclusion of structured PCK-focused training in teacher education curricula. Preservice training significantly enhances the PCK of future Islamic Religion teachers. Future research could explore the development of a digital literacy-based PCK model to inform the design of effective, subject-specific training programs across various educational disciplines.